Long-range anisotropic effects in a V–shaped Tröger's base diformanilide: Conformational study by NMR assignment and DFT calculations - Trupp, Leandro Julián (2018)
Herein we describe the synthesis and conformational analysis of a Tröger's base diformanilide whose distinctive NMR spectra was fully assigned via DFT calculations. The complexity of the spectra originated by the presence of three conformers in equilibrium shows that the nuclei in each side of the molecule are sensitive to the configuration not only of the closest formamide moiety but also of the farthest one, due to long–range anisotropic effects. The temperature and the solvent polarity influence were analyzed to determine the different conformer populations and the corresponding rotational activation parameters.